2001
DOI: 10.1177/109019810102800407
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Measures of Individual Perceptions of Community Social Dynamics: Results of a Community Survey

Abstract: This study examined how different measures of individual perceptions of community social dynamics relate to each other and how these measures relate to self-reported general health and depressive symptoms. Results of a principal components analysis conducted to investigate the interrelationships between these individual measures suggest that these measures measure separate phenomena. In addition, in results of multiple-regression analyses conducted to examine associations between the various measures of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 43 publications
2
71
0
Order By: Relevance
“…As results of various components of the stress process model were examined, 45,[51][52][53][54][55] findings were presented to the ESVHWP and discussed at regularly scheduled meetings, special community events, and Partnership retreats. These presentations and discussions greatly contributed to the clarity and depth of interpretation of the findings.…”
Section: Interpretation and Dissemination Of Results To The Communitymentioning
confidence: 99%
“…As results of various components of the stress process model were examined, 45,[51][52][53][54][55] findings were presented to the ESVHWP and discussed at regularly scheduled meetings, special community events, and Partnership retreats. These presentations and discussions greatly contributed to the clarity and depth of interpretation of the findings.…”
Section: Interpretation and Dissemination Of Results To The Communitymentioning
confidence: 99%
“…An important study in Detroit, however, identified greater sense of community (the strongest predictor), perceived neighbourhood control, and neighbourhood participation as independent predictors of better selfreported health and fewer depressive symptoms (93).…”
Section: Health and Development Outcomesmentioning
confidence: 99%
“…Starting in literacy education for slum dwellers and peasants in Brazil, Freire's work has been adapted worldwide in adult education (232- Two related concepts have been articulated by health professionals: community capacity and social capital. Community capacity is identified as containing ten dimensions, participation, support networks, sense of community and access to power (95), with processes and tools to measure capacity outcomes in development (38, 44,93,242). Social capital, or the norms and social networks that facilitate coordination for mutual benefit, has captured the imagination of health professionals largely because of epidemiologic studies that have correlated the variables of trust, reciprocity and civic engagement to morbidity/mortality statistics (68,(89)(90)(91).…”
Section: What Is the Evidence On Effectiveness Of Empowerment To Imprmentioning
confidence: 99%
“…Stronger community identity (or psychological sense of community) has been linked to lower depression (Koteskey, Little, & Matthews, 1991;Parker et al, 2001;Pretty, Conroy, Dugay, Fowler, & Williams, 1996;Stevens & Duttlinger, 1998) and lower anxiety (Sagy, 2002;Stevens & Duttlinger, 1998 In an interesting qualitative study by Sundberg (1995), participants wrote brief letters to three hypothetical target audiences (10-yr-old granddaughter, young parents, and a colleague) regarding their personal views about promotion of mental health (i.e., primary prevention). Content analysis showed several themes running throughout letters to all three target audiences, including the importance of having a sense of self-in-community.…”
Section: Community Group Identifications and Distress Or Well-beingmentioning
confidence: 99%
“…Content analysis showed several themes running throughout letters to all three target audiences, including the importance of having a sense of self-in-community. Parker et al (2001) surveyed neighborhood residents showing that psychological sense of community, perceived neighborhood control, and neighborhood participation were all associated with selfreported better general health and fewer depressive symptoms in separate regressions. But when all three of these predictors were added to regression models simultaneously, only psychological sense of community was significantly related to outcomes, suggesting perceived neighborhood control and neighborhood participation are part and parcel of psychological sense of community.…”
Section: Community Group Identifications and Distress Or Well-beingmentioning
confidence: 99%